Comparative Analysis of Fresh and Reclaimed Core Sand in Foundry Reuse Applications - Dugu, A.; Diószegi, A.; Elfsberg, J.E.; Domeij, B.B.; Hollinger, I.; Espinosa, M.P.; Nilsson, T.; Kindstedt, M. (Archives of Foundry Engineering, 2026)
This study examines chemical composition and grain morphology in fresh and reclaimed silica sand used for core production in an industrial iron foundry. The aim was to characterise in-house core sand before and after dry mechanical reclamation and to assess how repeated use affects element distribution and grain shape. Fresh and reclaimed sand samples from the core sand system were gathered and divided into standard size categories through sieving. The material was subsequently organised into fine, medium, and coarse layers using a stratified approach. X-ray fluorescence (XRF) was used to determine the chemical composition, while dynamic image analysis assessed grain shapes by examining roundness at the Q10, Q50, and Q90 percentiles. Selected samples were additionally examined using scanning electron microscopy (SEM). Reclaimed sand, especially fine particles (<0.125 mm), has higher levels of MgO, Al₂O₃, CaO, and C than fresh sand due to accumulated bentonite, binder residues, and dust. SiO2 remains the main component but is slightly lower in reclaimed material due to the higher share of these additional phases. Na₂O decreases slightly in reclaimed sand, while K₂O shows minimal variation between fractions and layers. Grain roundness differs only moderately and depends on size: fresh sand is more rounded in the fine fractions (63 μm and 90 μm), both sands have almost identical roundness in the 125–355 μm range, and reclaimed sand is only slightly more rounded in the coarse fractions (500–710 μm). Scanning electron microscopy (SEM) images indicate that both sand samples exhibit generally similar grain morphologies. However, differences in surface characteristics are likely attributable to a thin coating of fine clay and binder particles present on the reclaimed grains.